NRI gets new status - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Natural Resources Institute (NRI), the scientific arm of Britain's Overseas Development Administration, has a world-wide reputation for its expertise on renewable natural resources in developing countries. Its principal aim is to alleviate...